Stiffness Calculation for Negative Moment Region of Steel-Concrete Composite Beams considering the Influence of Cracking and Interface Slip - Wenlong Cao; Jianqing Bu; Cunbao Zhao; Xueyan Wang; Liping Zhang; Jiren Zhang (Advances in Materials Science and Engineering)
Concrete cracking and interface slip decrease the bending stiffness of steel-concrete composite beams (SCCBs) in the negative moment region. To evaluate this decrease in the stiffness of SCCBs, a static differential equation is used to derive analytical expressions of interface slip and deflection. Based on the static load test results for SCCBs, the influence of concrete cracking and interface slip on the stiffness is analyzed. A linear stiffness reduction method is proposed for calculating the stiffness of SCCBs in the negative moment region after the concrete undergoes cracking. The proposed method can be used in engineering applications as it enables the facile and accurate calculation of the deflection and slip and the changes in stiffness of SCCBs in the negative moment region. The method can also be used for predicting and evaluating performance in the field of structural design.